Effect of immune regulatory pathways after immunization with GMZ2 malaria vaccine candidate in healthy lifelong malaria-exposed adults. Issue 27 (2nd June 2020) - Nouatin, Odilon; Ateba Ngoa, Ulysse; Ibáñez, Javier; Dejon-Agobe, Jean Claude; Mordmüller, Benjamin; Edoa, Jean Ronald; Mougeni, Fabrice; Brückner, Sina; Bouyoukou Hounkpatin, Aurore; Esen, Meral; Theisen, Michael; Moutairou, Kabirou; et al.
Highlights: Immunization increases sHLA-G and Treg levels. Post immunization sHLA-G level decrease vaccine-specific antibody concentration. Pre and post immunization Treg level decrease plasmablasts frequency. High sHLA-G ratio is associated with risk of P. falciparum infection after CHMI. Abstract: Background: Despite appreciable immunogenicity in malaria-naive populations, many candidate malaria vaccines are considerably less immunogenic in malaria-exposed populations. This could reflect induction of immune regulatory mechanisms involving Human Leukocyte Antigen G (HLA-G), regulatory T (Treg), and regulatory B (Breg) cells. Here, we addressed the question whether there is correlation between these immune regulatory pathways and both plasmablast frequencies and vaccine-specific IgG concentrations. Methods: Fifty Gabonese adults with lifelong exposure to Plasmodium spp were randomized to receive three doses of either 30 µg or 100 µg GMZ2-CAF01, or 100 µg GMZ2-alum, or control vaccine (rabies vaccine) at 4-week intervals. Only plasma and peripheral blood mononuclear cells isolated from blood samples collected before (D0) and 28 days after the third vaccination (D84) of 35 participants were used to measure sHLA-G levels and anti-GMZ2 IgG concentrations, and to quantify Treg, Breg and plasmablast cells. Vaccine efficacy was assessed using controlled human malaria infection (CHMI) by direct venous inoculation of Plasmodium falciparum sporozoites (PfSPZ Challenge). Results: The sHLA-G concentration increased from D0 to D84 in all GMZ2 vaccinated participants and in the control group, whereas Treg frequencies increased only in those receiving 30 µg or 100 µg GMZ2-CAF01. The sHLA-G level on D84 was associated with a decrease of the anti-GMZ2 IgG concentration, whereas Treg frequencies on D0 or on D84, and Breg frequency on D84 were associated with lower plasmablast frequencies. Importantly, having a D84:D0 ratio of sHLA-G above the median was associated with an increased risk of P. falciparum infection after sporozoites injection. Conclusion: Regulatory immune responses are induced following immunization. Stronger sHLA-G and Treg immune responses may suppress vaccine induced immune responses, and the magnitude of the sHLA-G response increased the risk of Plasmodium falciparum infection after CHMI. These findings could have implications for the design and testing of malaria vaccine candidates in semi-immune individuals.